Observation on the clinical efficacy of delicate pulsed light combined with 1% pimecrolimus cream in the treatment of erythema telangiectasia rosacea - HU Xueying; HU Lingwei (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the clinical efficacy and safety of delicate pulsed light combined with 1% pimecrolimus cream for erythema telangiectasia rosacea. Methods Eighty patients with erythema telangiectasia rosacea were enrolled at the Second People's Hospital of Luohe from January 2022 to December 2022 and were randomly divided into the observation (41 cases) and control groups (39 cases). The observation group was treated with 1% pimecrolimus cream twice daily for 12 weeks and DPL once every 4 weeks for 3 times. The control group was treated with 1% pimecrolimus cream alone. The therapeutic effects and adverse reactions were compared between the two groups. Results Following 4, 8 and 12 weeks of the treatments, the skin lesion scores were 9.26±1.86, 7.91±1.87 and 5.95±1.46, respectively, in the observation group and were 11.38±1.36, 10.67±1.64 and 8.67±1.35, respectively, in the control group (t=3.26, 3.69, 4.12 and P=0.002, 0.001, 0.001 between the two groups). The effective rates were also differ significantly between the two groups at 4, 8 and 12 weeks (29.27% vs. 10.26%, 56.10% vs. 28.21% and 73.17% vs. 38.46%, respectively. P<0.05 for all). No apparent adverse reactions were observed in either group. Conclusion DPL combined with 1% pimecrolimus cream is an effective and safe method for erythema telangiectasia rosacea.